ANALISIS DAMPAK BANJIR TERHADAP KEADAAN SOSIAL EKONOMI MASYARAKAT DI KECAMATAN BADAR KABUPATEN ACEH TENGGARA - Sahadah, Nelda Sabatun (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
The socio-economic characteristics of society are changing. It can be seen from the social economy of the community which varies in terms of employment and home ownership. There were socio-economic changes in the community after the 2019 flash floods, the decline in the community's economy after the flash floods was caused by damage to agricultural land and road access to the village so that the income of the people in Natam and New Natam Villages experienced a decline. Changes in socio-economic characteristics after the flash flood occurred can be seen from house ownership and the decline in the community's economy caused by the destruction of the community's agricultural land. The difficulty of road access to the village has an impact on the cheap prices of agricultural products such as palm sugar, cocoa, rice, rubber latex, etc., so that people's income decreases.